Preferences and beliefs in a sequential social dilemma: A within-subjects analysis (2014)
In empirical analyses of games, preferences and beliefs are typically treated as independent. However, if beliefs and preferences interact, this may have implications for the interpretation of observed behavior. Our sequential social dilemma experiment allows us to separate different interaction channels. When subjects play both roles in such experiments, a positive correlation between first- and second-mover behavior is frequently reported. We find that the observed correlation primarily originates via an indirect channel, where second-mover decisions influence beliefs through a consensus effect, and the first-mover decision is a best response to these beliefs. Specifically, beliefs about second-mover cooperation are biased toward own second-mover behavior, and most subjects best respond to stated beliefs. However, we also find evidence for a direct, preference-based channel. When first movers know the true probability of second-mover cooperation, subjects' own second moves still have predictive power regarding their first moves. © 2014 Elsevier Inc.